Implementation of the ecohumanist concept in the Grand Maerakaca tourism space, Semarang, Indonesia - Sari, Suzanna Ratih; Muhammad, Fadhil; Hilmy, Muhammad Fariz (Turyzm/Tourism, 2024)
The aim of this study is to explain the implementation of ecotourism and the humanist (eco-humanist) perspective in the tourism space of Grand Maerakaca. This research has used qualitative methods to explore issues related to these concepts as implemented in Grand Maerakaca. Observations and interviews with tourists from various demographic segments were conducted to get information related to their ability to access ecotourism spaces. The results show that not all tourist providers in Grand Maerakaca implement the eco-humanist concept such as shown by the absence of local community participation and the empowerment of vulnerable groups. Besides, some tourist paths are inaccessible and dangerous for older tourists and children. Some of these are reasons why Grand Maerakaca is not attractive to tourists. The findings were analyzed using descriptive analysis techniques to obtain a perspective related to ecohumanist implementation in Grand Maerakaca. The output of this research is to suggest forms of this implementation in tourist spaces in Grand Maerakaca that can accommodate all tourists and can increase tourist visits.